Heterogeneity in Fluorescence-Stained Sperm Membrane Patterns and Their Dynamic Changes Towards Fertilization in Mice - Momoka Hirai; Satoshi Kishigami (Frontiers in Bioscience-Landmark)
Background: Sperm represent a heterogeneous population crucial for male reproductive success. Additionally, sperm undergo dynamic changes during maturation and capacitation. Despite these well-established processes, the complex nature of sperm heterogeneity and membrane dynamics remains elusive. The composition of phospholipids in the sperm membrane changes dynamically during maturation, with their release occurring during capacitation. This study aims to investigate the heterogeneity and dynamic changes in the sperm membrane during maturation and capacitation towards fertilization by visualizing these membrane dynamics. Methods: Sperm were collected from the cauda epididymis or testis of Institute of Cancer Research (ICR) male mice and stained with MemBright dye (commercial name: MemGlow™-560, MG-560), a fluorogenic live-cell membrane probe. Staining was performed either before, during, or after incubation for capacitation. In pre-staining experiments, sperm were stained with MG-560 before capacitation and then incubated to induce capacitation. Acrosome-reacted sperm were assessed after staining with peanut agglutinin FITC (PNA-Lectin FITC). Stained sperm were observed using fluorescence or confocal microscopy. Results: MG-560-stained sperm from the epididymis before capacitation showed four staining patterns: head-midpiece-tail (HMT), head-midpiece (HM), head (H), midpiece (M) positive, or totally negative, with ratios remaining unchanged during capacitation (30.5%, 29%, 11.3%, 3.7%, and 25.5%, respectively). In contrast, all testicular sperm were negative for staining. Pre-stained sperm exhibited an increased number of HM and M patterns over time, whereas the number of HMT-stained sperm decreased. Consistently, spontaneous acrosome-reacted sperm were detected predominantly in HM- or M-stained sperm. After in vitro fertilization (IVF) using pre-stained sperm, zona pellucida-attached sperm were mostly negative for staining. Finally, all sperm detected in the perivitelline space were only negative. Conclusions: Mature sperm membranes stained with MG-560 exhibited heterogeneous and dynamic changes during the capacitation and fertilization process. MG-560 staining identified sperm with the potential to undergo the acrosome reaction, and these MG-560-positive sperm eventually became negative as they penetrated the zona pellucida for fertilization. Thus, the MG-560 staining patterns likely reflect the physiological state and potential of the sperm. These findings provide new insights into sperm heterogeneity and dynamics, and this staining method may also prove useful for assessing sperm quality.